Pengaruh Job Demand terhadap Employee Welll-Being pada Karyawan Bagian Sales di Sumatera Barat - Zulia, Adisti Zainiah; Susanti, Roza Eva (ARZUSIN, 2025)
This research aims to examine the influence of job demand on employee well-being among cellphone sales employees in West Sumatra. Job demands are various physical, psychological, social, or organizational aspects of a job that require sustained physical and/or psychological effort, so that they are associated with certain physiological and/or psychological costs, while employee well-being is a positive emotional condition that reflects mental well-being, satisfaction at work, and happiness in life related to their overall work experience and role. This research uses a quantitative method with a correlational design. In this research, the sampling technique used was purposive sampling with data collected via a Google Form questionnaire involving 116 respondents from cellphone sales employees in West Sumatra. This research data was obtained using a Likert scale and then analyzed using simple regression analysis. Data analysis shows that there is a significant negative relationship between job demand and employee well-being with a contribution value of 78%. This shows that the higher the employee's job demands, the lower the welfare of cellphone sales employees.